2003
DOI: 10.1007/s00256-002-0590-0
|View full text |Cite
|
Sign up to set email alerts
|

Palmar dislocation of the trapezoid

Abstract: Palmar dislocation of the trapezoid is a rare injury, which results from substantial trauma to the wrist. It is associated with other bony or ligamentous injuries in the wrist. If unrecognized, loss of function of the hand and early osteoarthritis may result. Treatment of choice is open reduction and internal fixation, which generally achieves good functional results. We describe a new case of palmar dislocation of the trapezoid and review the world literature with emphasis on the radiographic findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 13 publications
(41 reference statements)
1
13
0
1
Order By: Relevance
“…1,4,16,17 Palmar dislocations of the trapezoid appear to be less common than dorsal dislocations because the palmar ligamentous attachments of the trapezoid are stronger than the dorsal ligaments. 12,13 Similar to our case, injury isolated to the STT with maintained relationship of the trapezoid and second metacarpal appears to be a less common variant that has been described infrequently in previous studies. 18 Due to the high-energy nature of these injuries, associated soft tissue injury frequently occurs.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…1,4,16,17 Palmar dislocations of the trapezoid appear to be less common than dorsal dislocations because the palmar ligamentous attachments of the trapezoid are stronger than the dorsal ligaments. 12,13 Similar to our case, injury isolated to the STT with maintained relationship of the trapezoid and second metacarpal appears to be a less common variant that has been described infrequently in previous studies. 18 Due to the high-energy nature of these injuries, associated soft tissue injury frequently occurs.…”
Section: Discussionsupporting
confidence: 85%
“…11 Dorsal dislocation is most common, although volar dislocations have been described. 12,13 Reports of trapezoidal dislocations have been isolated to case reports or small (<5 patient) case series, and isolated injuries represent the most uncommon variant of these cases.…”
mentioning
confidence: 99%
“…Isolated dislocation of the trapezoid may similarly occur in a volar [7, 19, 22, 23, 25, 51] or dorsal [1, 6, 11, 13, 2931, 35, 41, 42, 44, 47] direction. The trapezoid has a predisposition for dorsal dislocation due to exposure of the dorsal surface of the trapezoid during wrist extension, the constraints of the bony anatomy (particularly of the scaphoid) when the wrist is in dorsiflexion, and the presence of weaker ligaments dorsally than palmarly [1, 22, 2931, 38, 42, 44]. A mechanism for dorsal dislocation of the trapezoid due to a blow to the distal dorsal end of the second metacarpal with the wrist in slight flexion has been proposed [6, 2931, 47].…”
Section: Discussionmentioning
confidence: 99%
“…Wright and Umaar 8 describe "the missing carpal sign" as evidence of dorsal trapezoid dislocation, but this can be particularly challenging to evaluate in the setting of concomitant metacarpal dislocations. In their review, Koenig and West 9 found that a third of all trapezoid dislocations in the literature are missed on initial presentation. Broadbent et al 2 describe a case of trapezoid dislocation identified only on postoperative CT scan following fixation of CMC joints that required a return to the operating room for reduction.…”
Section: Journal Of Wrist Surgerymentioning
confidence: 99%